A backbone amide protecting group for overcoming difficult sequences and suppressing aspartimide formation. (18th April 2016) - Abdel‐Aal, Abu‐Baker M.; Papageorgiou, George; Raz, Richard; Quibell, Martin; Burlina, Fabienne; Offer, John
Abstract : A backbone amide bond protecting group, 2‐hydroxy‐4‐methoxy‐5‐nitrobenzyl (Hmnb), improved the synthesis of aggregation and aspartimide‐prone peptides. Introduction of Hmnb is automated and carried out during peptide assembly by addition of 4‐methoxy‐5‐nitrosalicylaldehyde to the peptidyl‐resin and on‐resin reduction to the secondary amine. Acylation of the hindered secondary amine is aided by the formation of an internal nitrophenol ester that undergoes a favourable O, N intramolecular acyl transfer. This activated ester participates in the coupling and generally gives complete reaction with standard coupling conditions. Hmnb is easily available in a single preparative step from commercially available material. Different methods for removing the amide protecting group were explored. The protecting group is labile to acidolysis, following reduction of the nitro group to the aniline. The two main uses of backbone protection of preventing aspartimide formation and of overcoming difficult sequences are demonstrated, first with the synthesis of a challenging aspartimide‐prone test sequence and then with the classic difficult sequence ACP (65‐74) and a 23‐mer homopolymer of polyalanine. Abstract : The use of backbone amide bond protection has dramatically improved the synthesis of peptides by Fmoc chemistry. We have developed 2‐hydroxy‐4‐methoxy‐5‐nitrobenzaldehyde, an easily prepared backbone‐protecting group. It can overcome the onset of difficult sequences and completely prevent aspartimide formation. The group can be removed by reduction and acidolysis or retained as desired for its solubilizing properties.